Peran Secretome dalam Terapi Osteoartritis - Mesya Azahra Putri; Ricky Edwin P. Hutapea; Norman Zainal (Pusat riset dan Inovasi Nasional, 2026)
Osteoarthritis is a progressive degenerative joint disease characterized by cartilage damage, chronic inflammation, and functional limitation. Current treatments mainly focus on symptom relief and mechanical correction, with limited ability to restore the biological environment of the joint. Recently, mesenchymal stem cell derived secretome has emerged as a promising cell free regenerative therapy with anti-inflammatory and tissue-repair potential. This study aimed to systematically review the role of mesenchymal stem cell secretome in osteoarthritis management, both as an intra-articular therapy and as an adjuvant following surgical intervention. A literature review was conducted on relevant preclinical and early clinical studies published over the past decade. The selected articles were analyzed to evaluate therapeutic mechanisms and clinical implications. The findings indicate that intra articular administration of secretome reduces inflammatory mediators, suppresses catabolic enzyme activity, and improves cartilage integrity in various osteoarthritis models. Early clinical evidence also suggests improvements in pain and joint function, especially in patients with mild to moderate disease. Furthermore, secretome shows potential as an adjuvant therapy after surgery by supporting biological recovery of joint tissues. Overall, mesenchymal stem cell secretome represents a promising component of a multimodal strategy for osteoarthritis management, although further clinical trials are required to confirm its efficacy and safety.